Disparities in healthcare providers' interpretations and implementations of ACIP's meningococcal vaccine recommendations. Issue 4 (2nd April 2020) - Huang, Liping; Goren, Amir; Lee, Lulu K.; Li, Vicky W.; Dempsey, Amanda; Srivastava, Amit
ABSTRACT: Invasive meningococcal disease (IMD) caused by the bacteria Neisseria meningitidis is rare but potentially fatal. For healthy adolescents, the US Advisory Committee on Immunization Practices (ACIP) recommends routine vaccination with MenACWY and recommends MenB vaccination under shared clinical decision-making (previously "Category B"). The recommendation for MenB vaccination was the first category B recommendation in adolescents, and it is unclear how healthcare providers (HCPs) implement these guidelines. This 2017 web-based survey of US HCPs explored characteristics associated with prescribing or receiving MenB and MenACWY vaccines, HCP knowledge of vaccine recommendations, and real-world practice patterns. Of 529 respondents, 436 prescribed MenB vaccines to their eligible adolescent/young adult patients and 93 prescribed MenACWY vaccines only. MenB vaccine prescribers were more likely to be pediatricians compared with MenACWY vaccine only prescribers, and patients who received MenB vaccines were more likely to be non-Hispanic whites living in shared spaces (eg, college dormitories) than those not receiving the vaccine. Seventy-seven percent of HCPs indicated that they prescribe MenACWY vaccines consistently with ACIP recommendations (to all members of an age group), whereas only 7% indicated that they prescribe MenB vaccines consistently with ACIP recommendations (individual clinical decision making). Patient-related factors, disease-related factors, and guidelines all influenced HCP decisions to prescribe meningococcal vaccines. Providing HCPs with clear guidance on how to initiate discussion of MenB vaccines with patients and their caregivers may aid in fully protecting US adolescents against meningococcal disease caused by 5 of the disease-causing serogroups.